Analysis of Strengths and Weaknesses of Locally Wisdom-Based Tourism Village: A Study of Sering Village, Pelalawan Regency, Riau Province, Indonesia - Muhammad Syafi’i; Dina Syaflita; M. Jaya Adi Putra; Naila Fauza; Ririn Jauharaini (Jurnal Penelitian Pendidikan IPA, 2025)
Analysis of potential and problems is necessary for developing the tourism concept. The potential and problems in Sering Village need to be mapped to obtain a comprehensive conclusion that is further required in the decision-making process. The analysis of this research can be processed through various decision-making techniques. This study aims to map the potential and problems in Sering Village in terms of government support, marketing potential of attractions and flagship products, and the human resources of the community as supporting factors. This type of research is qualitative descriptive research. The case study is focused on Sering Village, Pelalawan Regency, Riau Province, Indonesia. Data collection techniques involve interviews with village officials and 20 local residents. Solutions offered come from relevant literature reviews. Data analysis is descriptive, and the data obtained from local residents are analyzed descriptively with the help of charts. The results of this research show that the village's potential includes the attraction of local wisdom, Lake Sengkulim, close access to the winged palace, and the paper and pulp industry center, where access to the winged palace can be reached by land or river routes. Community involvement has been included in decision-making. There is already government cooperation with the industry to support environmental sustainability. The identified problems are the lack of specific regulations for tourism villages and the need to improve human resources related to tourism and marketing. Solutions that can be implemented include strengthening synergy with the government to expedite the approval of tourism village regulations and providing periodic training to improve the skills of the population related to tourism, product development, and marketing.